2020
DOI: 10.2147/ott.s234829
|View full text |Cite
|
Sign up to set email alerts
|

<p>HOXD9 Activates the TGF-β/Smad Signaling Pathway to Promote Gastric Cancer</p>

Abstract: Background: Gastric cancer (GC) is the most common malignant tumor of the digestive tract and its molecular mechanism is not clear. HOXD9 plays an important role in tumor progression as transcription factor. In the current study, we explored the role of HOXD9 in GC. Methods: We predicted the expression and potential mechanism of HOXD9 in GC through an online database. The expression of HOXD9 was detected in GC and adjacent tissues, and then we analyzed the relationship between HOXD9 and the prognosis of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Noteworthy, TGF-β plays a significant role in cancer progression. In enhancing migration and metastasis of cancer cells, TGF-β induces EMT through Smad4 upregulation ( Xiong et al, 2020 ). Upstream oncogenic factors such as HOXD9 stimulate expression of TGF-β, leading to enhanced proliferation and growth of tumor cells ( Wardhani et al, 2020 ).…”
Section: Transforming Growth Factor-beta Signaling Pathway: From Basimentioning
confidence: 99%
“…Noteworthy, TGF-β plays a significant role in cancer progression. In enhancing migration and metastasis of cancer cells, TGF-β induces EMT through Smad4 upregulation ( Xiong et al, 2020 ). Upstream oncogenic factors such as HOXD9 stimulate expression of TGF-β, leading to enhanced proliferation and growth of tumor cells ( Wardhani et al, 2020 ).…”
Section: Transforming Growth Factor-beta Signaling Pathway: From Basimentioning
confidence: 99%
“…We found that ANKRD53 was associated with Calcium, Hedgehog, MAPK, TGF-β signaling pathways, and pathways in cancer. All these signaling pathways have been reported to play critical roles in gastric cancer [ 28 , 29 ]. Although many reports have shown that CIN has an important value in gastric cancer, its related mechanisms are still unclear [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…HOXD9 is closely related to many kinds of tumors. It can promote tumorigenesis and metastasis by increasing the expression level of other genes in gastric and breast cancer ( Zhu et al, 2019 ; Xiong et al, 2020 ; Hu et al, 2022 ). Both HOXA10 and HOXD13 can promote the occurrence and development of various cancers by increasing the expression of genes and activating signal pathways ( Chen et al, 2019 ; Cui et al, 2020 ; Yin and Guo 2021 ), nevertheless, both of them can inhibit the expression of genes and suppress the occurrence of prostate cancer ( Hatanaka et al, 2019 ; Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%